On a submerged wave energy converter with snap-through power take-off - Wang, Lixian (2020)
This paper investigates the performance of a bistable snap-through power take-off (PTO) operating inside a submerged wave energy converter (WEC). The equation of motion of the surging WEC is derived in the time domain using the Euler–Lagrange equations. The dynamic response of the WEC in regular waves is studied first. It is found that the wave amplitude has a significant impact on the energy conversion efficiency with the proposed energy extraction mechanism. With larger waves impacting on the WEC, the conversion efficiency of the present nonlinear PTO increases significantly. Three response regimes, i.e. local oscillation, aperiodic snap-through, and periodic snap-through, of the nonlinear PTO system are observed with various wave amplitudes. This nonlinear feature is quite different from the linear PTO mechanism that is independent of the wave amplitude. Further, the dynamic response of the nonlinear WEC subjected to irregular wave sea conditions is investigated. Parametric studies have been carried out to determine the optimum operating conditions of the bistable device in order to maximize the wave energy extraction. The utilization of the snap-through PTO can enhance the efficiency of the WEC over its linear counterpart in irregular waves.